Identifying barriers and facilitators to implementing advance care planning in prisons: a rapid literature review - Ashley Macleod; Divya Nair; Ekin Ilbahar; Marcus Sellars; Linda Nolte (BMC, 2020)
Abstract Background Limited information is available describing advance care planning (ACP) within correctional facilities, despite its increasing relevance due to the ageing population in prisons and the high rates of complex medical comorbidities. In Western countries, self-determination with respect to making future medical decisions is a human right that prisoners do not lose when they are remanded into custody. ACP enables individuals to plan for their health and personal care so their values, beliefs and preferences are made known to inform future decision-making, for a time when they can no longer communicate their decisions. This paper examines the limited academic literature relating to ACP within prisons to identify barriers and facilitators that influence the uptake of ACP and advance care directive (ACD) documentation. Common themes related to ACP in a correctional setting were extracted and synthesised to produce a high-level analysis of barriers and facilitators influencing ACP uptake for prisoners within a correctional setting. Results Six articles met the selection criteria and reported on the experience of ACP and ACDs in prisons; five from the United States of America and one from Switzerland. Three dominant themes were identified, with related subthemes: system-level factors, attitudes and perceptions, and ACP knowledge and comprehension. Barriers to ACP and ACD implementation were more prominent in articles than facilitators. Conclusions Limited academic literature regarding the implementation and experience of ACP in prisons is available. The dominance of barriers identified in studies highlights key challenges for improving ACP uptake in correctional settings. Further research is required to understand the barriers, enablers, and attitudes to ACP in prisons.